Change Your Life in 7 Days : The World's Leading Hypnotist Shows You How - McKenna, Paul; Edited by Neill, Michael (London Bantam Press, 2004)
Learn how to master your emotions and run your own brain, how to have supreme self-confidence and become the person you really want to be. This title from Paul McKenna, author of "Unlimited Power", provides strategies and techniques for effective self-improvement.
The World's Leading Hypnotist Shows You How.
Keywords: Self-actualization (Psychology) -- Autogenic training -- Self-perception